ANALISIS PEMANFAATAN MEDIA BERBASIS VIDEO ANIMASI UNTUK MENINGKATKAN MINAT MAHASISWA DALAM PEMBELAJARAN MATA KULIAH IPS LANJUTAN DENGAN TEMA MEMPERTAHANKAN KEMERDEKAAN INDONESIA - Riang Tati, Andi Dewi Riang Tati (Universitas Muhammadiyah Palembang, 2024)
Effective learning is by utilizing technology. One form of utilizing this technology is the use of animated video media. Advanced Social Studies learning on a historical theme is considered one of the difficult and boring subjects for students of the Makassar State University Primary School Teacher Education Study Program (PGSD). This is because the learning media used is not interesting. This research aims to determine the perceptions of students and lecturers regarding the use of animated video media in advanced social studies learning. The type of research used is a case study or case study which is an empirical science to analyze phenomena in real life settings. This research requires 7 students from the class of 2023, class A4. Descriptive qualitative data analysis through data reduction in the form of summaries and centralizing data based on a learning interest questionnaire. The interviews conducted were explained in narrative form. Displaying data brings data that is then concluded. The research results found that the use of animated video media had a good impact on students' interest in learning.